Built heritage of chinese immigration in Historical Center of Lima - Chang Estrada, Angie (2020)
The article reflects on the consideration of the built heritage of the Chinese immigration in histori- cal center of Lima. For this, the relationship between heritage subjects and built heritage has been studied taking as reference the new positions on heritage. The investigation presents fourteen cases, grouped as: (i)a monumental zone, (ii) a monumental urban space, (iii) ten heritage buildings, and (iv) two landmarks and crosses them with two outlooks: internal and external to verify the existence of the built heritage of Chinese immigration in the Historical Center of Lima.